The Roll Back Malaria Partnership : Defining the role of the World Bank - World Bank (Washington, DC, 2012)
Malaria kills over one million people and causes 300-500 million episodes of illness each year. The majority of the 3,000 deaths each day and ten new cases every second occur in Africa. The disease not only takes a high human toll; it also impedes development. Malaria has economic impacts through labor efficiency and land use; adversely affects school attendance, performance and cognitive ability; and translates in monetary costs in terms of expenditures by households and the public health sector. The poor are affected most, as they have less access to services, information and protective measures (e.g. nets, screens, prophylaxis), and have less power to avoid living or working within malaria-affected areas. Malaria is on the rise. While efforts to control malaria in the past fifty years have achieved a decline in malaria mortality and morbidity in some regions, the gains have often not been sustained (e.g. Madagascar, Sri Lanka, Central Asia). Emerging drug and pesticide resistances threaten to reduce the availability of effective and affordable prevention and treatment of malaria. Recent epidemics indicate a resurgence of the disease in previously low-risk areas (e.g. the highlands of Kenya), and climate changes are expected to lead to further changes in intensity of transmission. While there is no magic bullet for malaria, a range of cost-effective interventions exists, namely antimalarials for treatment, prophylaxis, insecticide treated materials and residual spraying with insecticide. New tools are available and are continually being developed, such as treatment for severe malaria, rapid diagnostic tests, and combination drug therapy to prevent resistance. As access to prevention, diagnosis and treatment are essential to reducing the burden; malaria can only be effectively controlled within the context of broader health sector development. The main strategies for addressing malaria are timely care-seeking, diagnosis and effective treatment, the use of prophylaxis during pregnancy, and the use of insecticide-treated bednets and materials.